Air transport carbon reduction optimization based on low carbon emissions. Issue 1 (February 2020) - Lin, Wei
Abstract: Nowadays, with the deepening of environmental protection concept, low-carbon transportation has gradually become the mainstream trend, the environmental cost of airport emissions research will gradually arouse social concern. Real low-carbon transport has become a country to achieve low-carbon energy saving, win the low-carbon war, sustainable development of the only way. Through the analysis of transportation costs and carbon emission costs related to aviation networks, reference to domestic and foreign calculation methods for carbon emissions environmental costs, the establishment of airport environmental cost model, through the analysis of pollutant components to reduce the cost of emission control, so as to reduce operating costs and achieve carbon emission reduction.